Lowly methylated region analysis identifies EBF1 as a potential epigenetic modifier in breast cancer. Issue 11 (2nd November 2017) - Fernandez-Jimenez, Nora; Sklias, Athena; Ecsedi, Szilvia; Cahais, Vincent; Degli-Esposti, Davide; Jay, Antonin; Ancey, Pierre Benoit; Woo, Hae Dong; Hernandez-Vargas, Hector; Herceg, Zdenko
ABSTRACT: Breast cancer (BC) encompasses heterogeneous pathologies with different subtypes exhibiting distinct molecular changes, including those related to DNA methylation. However, the role of these changes in mediating BC heterogeneity is poorly understood. Lowly methylated regions (LMRs), non-CpG island loci that usually contain transcription factor (TF) binding sites, have been suggested to act as regulatory elements that define cellular identity. In this study, we aimed to identify the key subtype-specific TFs that may lead to LMR generation and shape the BC methylome and transcription program. We initially used whole-genome bisulfite sequencing (WGBS) data available at The Cancer Genome Atlas (TCGA) portal to identify subtype-specific LMRs. Differentially methylated regions (DMRs) within the BC PAM50 subtype-specific LMRs were selected by comparing tumors and normal tissues in a larger TCGA cohort assessed by HumanMethylation450 BeadChip (450K) arrays and TF enrichment analyses were performed. To assess the impact of LMRs on gene expression, TCGA RNA sequencing data were downloaded and Pearson correlations between methylation levels of loci presenting subtype-specific TF motifs and expression of the nearest genes were calculated. WGBS methylome data revealed a large number of LMRs for each of the BC subtypes. Analysis of these LMRs in the 450K datasets available for a larger sample set identified 7, 765, 5, 657, and 19 differentially methylated positions (DMPs) between normal adjacent tissues and tumor tissues from basal, luminal, and HER2-enriched subtypes, respectively. Unsupervised clustering showed that the discriminatory power of the top DMPs was remarkably strong for basal BC. Interestingly, in this particular subtype, we found 4, 409 differentially hypomethylated positions grouped into 1, 185 DMRs with a strong enrichment for the early B-cell factor 1 (EBF1) motifs. The methylation levels of the DMRs containing EBF1 motifs showed a strong negative correlation with the expression of 719 nearby genes, including BTS2 and CD74, two oncogenes known to be specific for basal BC subtype and for poor outcome. This study identifies LMRs specific to the three main BC subtypes and reveals EBF1 as a potentially important regulator of BC subtype-specific methylation and gene expression program.